Exploring disorder in the spin gapless semiconductor Mn2CoAl. (4th September 2019) - Buckley, Robert G; Butler, Tane; Pot, Catherine; Strickland, Nicholas M; Granville, Simon
Abstract: Since the prediction of spin gapless semiconducting behaviour in the Heusler compound Mn2 CoAl, evidence of spin gapless behaviour in thin films has typically been inferred from magnetotransport measurements. The spin gapless state is however fragile, and further, band structure calculations indicate that even a small amount of atomic disorder may destroy it. To explore the impact of disorder on the properties of Mn2 CoAl, we have undertaken an experimental study of the structural, magnetotransport and optical properties from the far infrared to the UV, on DC magnetron sputtered Mn2 CoAl thin films. A very short mean free path, of the order of a lattice spacing, is extracted from the DC transport data. A room temperature resistivity of 200 μ Ωcm along with a small and negative temperature coefficient of resistance between 4 and 400 K was measured. We note that parameters of this magnitude are often observed in disordered metals. We find this behaviour is well described by a weak localisation model, a result that is supported by a large Drude contribution to the optical response, where a high scattering rate is derived, which is equal to the value derived from the DC conductivity and Hall effect data. We also note the strong similarities between the magnetotransport behaviour reported for Mn2 CoAl films in the literature, including ours. We conclude that, based on comparisons between the experimental data, and recent band structure calculations that explicitly include disorder, as-prepared Mn2 CoAl films are best described as a disordered metal, rather than a spin gapless semiconductor.